“Cavity spilling” perforation during recanalisation of the right coronary artery – reocclusion of the recanalised artery as a method of emergency treatment - Kurianowicz, Marek; Zapolski, Tomasz; Wróbel, Robert; Drozd, Jakub (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Coronary artery perforation is an uncommon but potentially life-threatening complication of percutaneous coronary interventions. We report a case of a 78-year-old patient with “cavity spilling” right coronary artery perforation leading to formation of a fistula with contrast spilling directly to the right ventricle which occurred during recanalisation of the chronically occluded coronary artery. This rare complication was treated with a polytetrafluoroethylene-covered stent graft implanted into the right ventricular artery at the site of the right ventricular branch, followed by reocclusion of the right coronary artery and complete patient recovery. A control coronary angiography after 6 months has been scheduled.